2015
DOI: 10.1039/c4ce00408f
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine magic: one new organofluorine linker leads to three new metal–organic frameworks

Abstract: 2-Fluoro-1,3,5-benzene-tricarboxylic acid (Fbtc) is used as new linker for metal–organic frameworks and leads to three MOFs UHM-31, -32 and -33.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 41 publications
(25 reference statements)
5
47
0
Order By: Relevance
“…Fröba et al incorporated 2-fluoro-1,3,5-benzene-tricarboxylate (mfBTC 3-) in three copper containing MOFs/CPs named UHM-31, -32, and -33. [10] Especially UHM-31 is of interest, as it represents a fluorinated isostructural analogue of HKUST-1. The reported H 2 uptake of UHM-31 is only slightly higher than that of HKUST-1, but the CO 2 adsorption is increased significantly compared to HKUST-1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fröba et al incorporated 2-fluoro-1,3,5-benzene-tricarboxylate (mfBTC 3-) in three copper containing MOFs/CPs named UHM-31, -32, and -33. [10] Especially UHM-31 is of interest, as it represents a fluorinated isostructural analogue of HKUST-1. The reported H 2 uptake of UHM-31 is only slightly higher than that of HKUST-1, but the CO 2 adsorption is increased significantly compared to HKUST-1.…”
Section: Introductionmentioning
confidence: 99%
“…The reported H 2 uptake of UHM-31 is only slightly higher than that of HKUST-1, but the CO 2 adsorption is increased significantly compared to HKUST-1. [10] Fröba et al used a reported procedure for the synthesis of 2-fluoro-1,3,5-benzene-tricarboxylic acid (H 3 mfBTC), [11] which is commercially not available. It is remarkable that for the synthesis of UHM-31 a different Cu 2+ :linker ratio was used (1.63:1) [10] than for the synthesis of HKUST-1 (1.8:1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selfassembly of organic molecules and metal ions is a well known strategy for the construction of coordination polymers. The uorine substituted organic molecules are good candidates for construction of functional coordination polymers because they are more stable against oxidation and show enhanced thermal stability [6]. The penta uorobenzoate as ligand has been reported in some studies, while only few complexes with 2,6-di uorobenzoate (dfba) have been reported [7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…However, polynuclear clusters with fascinating structures and properties which are constructed by benzoic acids have been reported [10,11]. Meanwhile, the coordination polymers based on fluorine substituted organic molecules are found to be more stable to oxidation and show enhanced thermal stability [12].…”
Section: Commentmentioning
confidence: 99%